Strategi Pengelolaan dan Pengembangan Perpustakaan untuk Meningkatkan Minat Baca di SMA N 3 Medan - Luthfi Hafizah Harahap, luthfi; Nurhayani Nurhayani; Rholand Muary (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the strategy of library management and development in increasing reading interest in SMAN 3 Medan and identify factors that influence students' reading interest. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that library management and development at SMA N 3 Medan play a crucial role in increasing students' reading interest. The strategies implemented include the procurement of a varied book collection that is relevant to students' needs, improving the quality of library services, and creating a comfortable and conducive environment for reading. In addition, the library also acts as a center for literacy activities by holding various programs such as book discussions, interactive reading corners, and digital literacy training. This study also found that students' reading interest at SMA N 3 Medan was influenced by various factors, including the school environment, availability of library facilities, students' intrinsic motivation, family support, and social and cultural influences. Supportive school environmental factors, such as proactive school policies in improving literacy and the role of teachers in encouraging students to read, also contributed to increasing reading interest.